Analisis Nilai Moral Serial Televisi Upin dan Ipin Dikalangan Anak-Anak - Selpi Vera; Asnawati Asnawati; Yanto Yanto (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
The background of this research is the presence of the serial film Upin Ipin is one of the da'wah strategies that can convey messages of kindness to others. Because in the Upin Ipin series there are many moral values, which invite goodness. The purpose of this research is to describe the moral values in the television series Upin Ipin among children. In this study, the theory used is social learning theory (Albert Bandura) which is an individual's cognitive process that plays a role in learning. with the stages of attention, memory, reproduction, and motivational. From the results of research on the Upin Ipin series, there are several moral values that teach us, especially children who watch to always do good and perform fardhu prayers, Koran, taraweh and fasting in the month of Ramadan. Thus, children who watch the Upin Ipin series will pay attention to behavior and words and imitate or imitate the behavior found in the series. From the results of the analysis, there are three moral values contained in the Upin Ipin series, including moral values towards God (taqwa), moral values towards family (obedience to parents, mutual love), moral values towards society (tolerance and friendliness to friends). The conclusion from the results of this study is the positive value that can be drawn from the Upin Ipin serial program, namely in the aspect of moral values, this event shows learning with social learning theory used, children can pay attention to the Upin Ipin serial they watch, and they can learn various things, especially in religion, namely prayer, taraweh, fasting, by paying attention to the behavior in the series. Children remember in their memory the positive lessons in the series and will practice them in everyday life.